IMPLEMENTASI PEMBELAJARAN TEMATIK DI SD N KEMASAN 1 POLOKARTO: IMPLEMENTASI PEMBELAJARAN TEMATIK DI SD N KEMASAN 1 POLOKARTO - Suswandari, Meidawati (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2021)
This study aims to describe the implementation of thematic learning in SD N Kemasan 1, Polokarto. This research use desciptive qualitative approach. The sampling technique used purposive sampling. The informants in this study were teachers and fifth grade students of SD N Kemasan 1 Polokarto. Data collection techniques used include observation and documentation. Data analysis using data reduction techniques, data presentation, and drawing conclusions. The results showed that the thematic learning process at SD N Kemasan 1 Polokarto includes 1) learner-centered. 2) provide direct experiences to students (direct experiences) 3) the separation between subjects is not so real and clear. 4) presents a concept from various subjects in a learning process 5) flexible or flexible. 6) learning outcomes are in accordance with students' interests and needs because students are given the opportunity to optimize their potential according to their wishes.